2015
DOI: 10.1016/j.heliyon.2015.e00036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerosol vertical distribution on aerosol-radiation interaction: A theoretical prospect

Abstract: This study presents a theoretical investigation of the effect of the aerosol vertical distribution on the aerosol radiative effect (ARE). Four aerosol composition models (dust, polluted dust, pollution and pure scattering aerosols) with varying aerosol vertical profiles are incorporated into a radiative transfer model. The simulations show interesting spectral dependence of the ARE on the aerosol layer height. ARE increases with the aerosol layer height in the ultraviolet (UV: 0.25–0.42 μm) and thermal-infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 65 publications
(67 reference statements)
5
39
0
Order By: Relevance
“…Differences in the DARF are very low at both levels, with mean differences of -0.001 Wm -2 (standard deviation of 0.009 Wm -2 ) at the SURF, and of 0.012 Wm -2 (standard deviation of 0.050 Wm -2 ) at the TOA. These results are in line with the sensitivity study performed by Mishra et al (2015), who concluded that aerosol forcing in the visible-near infrared range is less sensitive to changes in the aerosol layer height as compared to thermal-infrared and ultraviolet ranges.…”
Section: Aerosol Radiative Forcingsupporting
confidence: 92%
“…Differences in the DARF are very low at both levels, with mean differences of -0.001 Wm -2 (standard deviation of 0.009 Wm -2 ) at the SURF, and of 0.012 Wm -2 (standard deviation of 0.050 Wm -2 ) at the TOA. These results are in line with the sensitivity study performed by Mishra et al (2015), who concluded that aerosol forcing in the visible-near infrared range is less sensitive to changes in the aerosol layer height as compared to thermal-infrared and ultraviolet ranges.…”
Section: Aerosol Radiative Forcingsupporting
confidence: 92%
“…3), which is expected due to the different geographical areas and periods of interest between the two studies. The smooth reduction with increasing wavelength in the SSA of pure soot in this study, as well as the abrupt decrease from 1 to 3 µm in the water-soluble aerosol modes, is consistent with the findings of Mishra et al (2014Mishra et al ( , 2015 for the polluted air masses over the Mediterranean as well as with the respective model values used in the study by Takemura et al (2002) for carbonaceous and sulfate aerosol.…”
Section: The Aerosol Optical Propertiessupporting
confidence: 91%
“…δ(AOD) can be calculated using Equation (9). Considering that the MODIS TOA brightness temperature errors are 0.25 K for channels 28, 33, 34 and 35, 0.05 K for channels 29, 31 and 32, and 0.35 K for channel 36, respectively, δ(L DSLR ) can be acquired with Equation (8).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…DSLR is the result of atmospheric scattering, absorption and emission in the entire vertical column, and it can be accurately calculated with complex radiative transfer models for which the concentrations of atmospheric constituents and the vertical distribution of temperature, water vapor, aerosol and clouds as the input parameters [4][5][6][7]. It is therefore necessary to evaluate accurately these parameters if one wants to reduce uncertainties in computing their radiative effects [8,9]. However, acquisition of these parameters is difficult and they are varying rapidly, at a daily or even hourly scale.…”
Section: Introductionmentioning
confidence: 99%